Ingelara Grazing: Leucaena in speargrass country, Queensland, Australia - Stuart Ogg; Sheree Ogg (Tropical Grasslands-Forrajes Tropicales, 2019)
Poster presented at the International Leucaena Conference, 1‒3 November 2018, Brisbane, Queensland, Australia.